2013
DOI: 10.1128/ec.00150-13
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Bacterial Lipopolysaccharide-Recognizing G-Protein-Coupled Receptor in the Bacterial Engulfment by Entamoeba histolytica

Abstract: Entamoeba histolytica is the causative agent of amoebic dysentery, a worldwide protozoal disease that results in approximately 100,000 deaths annually. The virulence of E. histolytica may be due to interactions with the host bacterial flora, whereby trophozoites engulf colonic bacteria as a nutrient source. The engulfment process depends on trophozoite recognition of bacterial epitopes that activate phagocytosis pathways. E. histolytica GPCR-1 (EhGPCR-1) was previously recognized as a putative G-protein-couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Protists are well-known bacterivores. Entamoeba and Blastocystis can graze on bacteria ( 43 , 44 ), and this is an important mechanism for the top-down control of bacterial communities due to their high feeding rates ( 45 ). It was also recently reported that Trichuris muris , a nematode from the mouse gut, acquires its intestinal microbiota from the mouse intestine, very likely through ingestion ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protists are well-known bacterivores. Entamoeba and Blastocystis can graze on bacteria ( 43 , 44 ), and this is an important mechanism for the top-down control of bacterial communities due to their high feeding rates ( 45 ). It was also recently reported that Trichuris muris , a nematode from the mouse gut, acquires its intestinal microbiota from the mouse intestine, very likely through ingestion ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial predation is also known to occur in the case of a group of free-living amoebas, which are the only group of organisms that can cause a decrease of a bacterial population from 10 8 down to 10 5 per gram of soil ( 58 , 59 ). Bacterial engulfment has also been described during colonization by the intestinal protist Entamoeba histolytica ( 60 ). Interestingly, a previous study showed that the presence of Entamoeba (likely including E. histolytica and E. dispar ) was associated with an effect on Prevotellaceae and Ruminococcaceae that was similar to what we found in this study ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since cells are endowed with a rich layer of glycans (glycoproteins and glycolipids) on their plasma membrane, a plausible working hypothesis is that glycoconjugates and glycan‐binding proteins (e.g., lectins, LPS, LPPG, and glycocalyx) are the best candidates for recognition between amoebae and diverse cells (Cummings, 2019) or for recognition at the ameba surface of ligands that induce intracellular signaling. For instance, LPS is recognized by E. histolytica (Brewer et al, 2013), and human galectin 1 and 3 are secreted by human liver cells upon their interaction with amebic trophozoites (Petropolis et al, 2014). According to this hypothesis, the amebic surface lectins, including the Gal/GalNAc lectin, co‐receptors, as well as other proteins less studied or potentially to be discovered, are the main candidates for the recognition of signals on the human cells surface (Figure 4b).…”
Section: Signals and Signaling Involved In Engulfment Of Human Cells By E Histolyticamentioning
confidence: 99%
“…The β1‐adrenergic receptor is a surface G protein‐coupled receptor (GPCR) (Hall, 2004) that recognizes ligands, such as catecholamines through its extracellular N‐terminal domain. In humans, there are over 800 GPCRs (Sutkeviciute & Vilardaga, 2020), but no GPCR receptor implicated in amoebic encystation has been described so far, although other GPCRs have been found in E. histolytica (Agarwal et al, 2020; Brewer et al, 2013; Ehrenkaufer et al, 2007; Picazarri et al, 2005).…”
Section: Signals and Signaling Involved In Encystation Of Entamoebidaementioning
confidence: 99%